Aggregatibacter actinomycetemcomitans: Important pathogen in periodontitis - Ramos Perfecto, Donald (2010)
Aggregatibacter actinomycetemcomitans is a pathogen extensively studied in the clinical conditions of the Periodontitis, already identified in the early twentieth century. Over the years it has undergone changes in its denomination and multiple virulence factors that make it an important pathogen in the periodontal disease have been discovered, specifically in the localized Aggressive Periodontitis. This review tries to explain its morphology, virulence factors, culture and other important characteristics.